2017
DOI: 10.1002/jcb.25994
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrocostus Lactone Suppresses Proliferation of Human Chronic Myeloid Leukemia Cells Through Bcr/Abl‐JAK/STAT Signaling Pathways

Abstract: This study evaluates the anticancer effects of dehydrocostus lactone, a plant-derived sesquiterpene lactone, on human chronic myeloid leukemia cells. Dehydrocostus lactone significantly inhibits cell proliferation by inducing cells to undergo cell cycle arrest, apoptosis, and differentiation. Dehydrocostus lactone suppresses the expression of cyclin B1, cyclin A, cyclin E, cyclin-dependent kinase 2 (CDK2), and cyclin-dependent kinase 1 (CDK1) and increases p21 expression, resulting in S-G2/M phase arrest in K5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…The study from Li Lin et al has shown that the STAT3 inhibitor FLLL32 inhibits the expression of CCND1, which is one of the STAT3 downstream targets in cancer cells. 33 Previous studies have revealed that JAK2 mediates the increase in c-Myc expression in CML cells, 34 while the increase expression of Bcl-xL is associated with activation of JAK2 and STAT3 23 . Consistent with our data, Ma Lingdi and co-workers have found that inactivation of JAK2/STAT3 and down-regulation of c-Myc and CCND1 induced cell cycle arrest in K562 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study from Li Lin et al has shown that the STAT3 inhibitor FLLL32 inhibits the expression of CCND1, which is one of the STAT3 downstream targets in cancer cells. 33 Previous studies have revealed that JAK2 mediates the increase in c-Myc expression in CML cells, 34 while the increase expression of Bcl-xL is associated with activation of JAK2 and STAT3 23 . Consistent with our data, Ma Lingdi and co-workers have found that inactivation of JAK2/STAT3 and down-regulation of c-Myc and CCND1 induced cell cycle arrest in K562 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expressions of myeloid differentiation markers (CD11b, CD11c and CD14) were detected by flow cytometry. [21][22][23] Only the level of CD11b and CD14 were slightly higher in KO cells than in WT cells, but these changes were not statistically significant (Supplement Fig. 1D).…”
Section: Deletion Of Mbd2 Inhibits the Proliferation Of K562 Cells Inmentioning
confidence: 92%
“…Bortezomib can induce apoptosis of K562 leukemic cells by interacting with JAK/STAT pathway (29). JAK/STAT signaling pathway is found to mediate sehydrocostus lactone-suppressed proliferation of CML cells (30). In this study, overexpression of miR-574-3p could inhibit the activation of JAK/STAT3 pathway, which was rescued by overexpression of IL6.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies demonstrated that Stat5 is the major downstream target of Bcr/Abl and that inhibition of Bcr/Abl could significantly downregulate the levels of Stat5 (Berger et al, ). In addition, Bcr/Abl/Stat5 inhibition induced apoptosis in CML cells by suppressing Stat5‐dependent transcriptional regulation of Bcl‐2 family members such as Mcl‐1, Bcl‐2, and Bcl‐xL (Cai, Qin, & Yang, ; Wang et al, ). Therefore, targeting Bcr/Abl tyrosine activity and Stat proteins to induce cell apoptosis and reduce proliferation is a promising approach for anti‐CML drug development.…”
Section: Introductionmentioning
confidence: 99%